2021
DOI: 10.3390/ijms22157865
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgal Defense against Competitors and Herbivores

Abstract: Macroalgae are the source of many harmful allelopathic compounds, which are synthesized as a defense strategy against competitors and herbivores. Therefore, it can be predicted that certain species reduce aquaculture performance. Herein, the allelopathic ability of 123 different taxa of green, red, and brown algae have been summarized based on literature reports. Research on macroalgae and their allelopathic effects on other animal organisms was conducted primarily in Australia, Mexico, and the United States. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 166 publications
(210 reference statements)
0
8
0
Order By: Relevance
“…One possible explanation for some of the negative effects caused by our macroalgae may be a combination of exploitative competition and allelopathy. Only a few previous studies (Friedlander et al 1996, Xu et al 2012) have investigated allelopathy between macroalgal species, while macroalgal allelopathy on corals is fairly well studied (reviewed by Budzałek et al 2021). Unlike Padina or Sargassum , Galaxaura is known to be strongly allelopathic to corals, although this was demonstrated for a congener to our study species (Rasher and Hay 2010, 2014, Rasher et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for some of the negative effects caused by our macroalgae may be a combination of exploitative competition and allelopathy. Only a few previous studies (Friedlander et al 1996, Xu et al 2012) have investigated allelopathy between macroalgal species, while macroalgal allelopathy on corals is fairly well studied (reviewed by Budzałek et al 2021). Unlike Padina or Sargassum , Galaxaura is known to be strongly allelopathic to corals, although this was demonstrated for a congener to our study species (Rasher and Hay 2010, 2014, Rasher et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…compared to the control. In other works, Budzałek et al (2018Budzałek et al ( , 2021b and Złoch et al (2018) demonstrated that extract and filtrate of U. intestinalis containing water-soluble allelochemical(s) is able to influence the fluorescence parameters of some Baltic cyanobacteria. Budzałek et al (2018) noted that the highest decrease in Fv/Fm for Nostoc sp.…”
Section: Ulva Intestinalis On Photosynthesis Performancementioning
confidence: 97%
“…All that is required is a shift in thinking so that the response of the system to a basket of stressors dominates the debate rather than the current silo approach of looking at the dose of single stressors in isolation. In chemical ecology, the chemicals function as highly sensitive communicators of information to receptors [ 76 , 77 , 78 , 79 , 80 , 81 ]. These may be predators responding to messages alerting them to the presence of prey (known as kairomones), prey responding to signals from predators (allomones) or signals from potential mates (pheromones).…”
Section: Chemical Ecology Mychorrysal and Microbiome Evidencementioning
confidence: 99%